Numerical investigation of the effect of convex transverse curvature and concave grooves on the turbulent boundary layer along a cylinder in axial flow - Wachter, Florian; Metelkin, Alexander; Jovanović, J.; Praß, Julian; Becker, Stefan (International Journal of Heat and Fluid Flow, 2021)
Axisymmetric turbulent boundary layers that develop around streamwise oriented long cylinder-like objects can be found in many applications, such as towed array sonars or marine seismic streamers. In many of these applications, turbulent fluctuations within the boundary layer flow can have a negative impact compared with laminar flow conditions. The aim of the present work is to design a surface modification that influences the turbulent boundary layer around a cylinder in axial flow in order to reduce turbulent fluctuations. To design the surface we consider recent findings regarding the turbulence damping effects of groove-like surface structures and combine these insights with the effect of convex transverse curvature on turbulence. We use large-eddy simulations to investigate the flow around a cylinder of modified design and around a reference circular cylinder. Both flows have a radius-based Reynolds number of Rea≈1.23⋅104" role="presentation">. The modified design leads to a 20 % decrease in the average wall shear stress and results in local reductions in the turbulent intensities, Reynolds stress, the temporal velocity spectrum, and the turbulent dissipation rate. The analysis within the anisotropy-invariant space reveals a tendency towards flow relaminarization. However, the new design has no effect on turbulent pressure fluctuations. We provide suggestions on how to further improve the surface design to achieve even greater flow stabilizatio
CRIS-Team Scopus Importer:2021-10-01
Keywords: Axial cylinder flow; Axisymmetric turbulent boundary layer; Flow control; Seismic streamer; Surface modification; Towed array sonar

Statistical interpretation of LDA measurements in naturally developing turbulent drag-reducing flow using invariant theory - Moataz, Mohammad; Reiter, Nina; Al-Mqbas, Mona; Metelkin, Alexander; Latifi, A.; Jovanović, J.; Delgado, Antonio (International Journal of Heat and Fluid Flow, 2022)
Turbulent drag reduction by an extremely diluted aqueous solution of polyacrylamide was studied in a fully developed plane channel flow under non-tripped flow conditions allowing the natural development of turbulence presumably from the initially laminar like a flow state. Using laser-Doppler anemometry, all components of the Reynolds stress tensor were measured. This permitted the determination of the turbulence anisotropy and independent invariants of the anisotropy tensor. Introducing a measure for the departure of the Reynolds stress tensor from the statistically axisymmetric state that ensures laminarity, fundamental insights relating the origin of turbulence and turbulent drag reduction were analyzed in light of the measured results and existing databases of direct numerical simulations. The chief mechanism relevant to the onset of turbulence and turbulent drag reduction deduced from analytic considerations involving only kinematic constraints was confirmed by the experimental data. Parametrization of the drag reduction effect in terms of the Deborah number based on turbulence quantities evaluated at the wall supports the deduction of the polymer-turbulence interaction in terms of the elastic properties of the polymer and the near-wall turbulence structure.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Turbulence measurements; Turbulence modeling; Turbulence simulation; Turbulent drag reduction